Electrical Vehicle Battery Cooling by Thermoelectric Cooling Module - Suksusron, Punyawee; Wiriyasart , Songkran; Naphon , Paisarn (Srinakharinwirot University Engineering Journal, 2021)
In this paper, a study on electrical vehicle battery cooling by the thermoelectric module using ferrofluid (Fe3O4) as a coolant is presented. The parametric study that affects the heat transfer and flow characteristic at the hot side mainly focuses the heat sink with water and ferrofluid concentration 0.005% and 0.015% as the coolants, the mass flow rate of coolant that providing the optimum heat transfer characteristic for EV battery cooling is investigated. The battery pack was embedded at the cold side of the thermoelectric cooler module is a cylindrical 18650 cell type has connected a series of 6S and a parallel of 10P(6S10P). The total output voltage/current of the battery pack will be 22.2 – 25.2 V /34Ah is obtained. The result has shown that Ferrofluids as a coolant is better than that water in thermal performance. Moreover, Ferrofluid concentration of 0.015% has a higher thermal performance than that of 0.005% and water of 20% and 30% are obtained. The obtained results will be a guidance for improvement in the EV battery cooling in the future.